Diversity of algae and lichens in biological soil crusts of Ardley and King George islands, Antarctica. Issue 3 (12th January 2017) - Borchhardt, Nadine; Schiefelbein, Ulf; Abarca, Nelida; Boy, Jens; Mikhailyuk, Tatiana; Sipman, Harrie J.M.; Karsten, Ulf
Abstract: In the present study the biodiversity of the most abundant phototrophic organisms forming biological soil crust communities were determined, which included green algae, diatoms, yellow-green algae and lichens in samples collected on Ardley and King George islands, Maritime Antarctic. The species were identified by their morphology using light microscopy, and for lichen identification thin layer chromatography as also used to separate specific secondary metabolites. Several sources of information were summarized in an algae catalogue. The results revealed a high species-richness in Antarctic soil crust communities with 127 species in total. Of which, 106 taxa belonged to algae (41 Chlorophyta, nine Streptophyta, 56 Heterokontophyta) and 21 to lichens in 13 genera. Moreover, soil crust communities with different species compositions were determined for the various sampling locations, which might reflect microclimatic and pedological gradients.